Agrawal nanofluid flow towards a stagnation point past a moving disk with smoluchowski temperature and Maxwell velocity slip boundary conditions: The case of Buongiorno's model. Issue 3 (8th December 2022) - Khan, Umair; Zaib, Aurang; Ishak, Anuar; Waini, Iskandar; Wakif, Abderrahim; Galal, Ahmed M.
Abstract: Nanofluid is a novel heat transfer fluid with the ability to significantly improve the heat transfer efficiency of regular fluids. Many efforts have been made to study its viscosity and thermal conductivity, both of which are crucial thermophysical properties. This work reports the significance of nanofluid along with thermophoretic and Brownian motion phenomena on the Agrawal flow towards a stagnation point past a permeable moving disk. The impacts of the Maxwell velocity slip and Smoluchowski temperature conditions are also incorporated. The leading equations in form of PDEs (Partial differential equations) are simplified into ODEs (Ordinary differential equations) by employing similarity theory. Then these simplified equations are solved numerically by utilizing a bvp4c solver (fourth‐order boundary value problem).The phenomenal effects of the relevant embedded distinguished parameters on the shear stress, rate of mass, and heat transfer are demonstrated through different graphs and tables. Graphical results indicate that double solutions are detected for stretching/shrinking parameter in a certain range. The heat transport and the wall drag force ascend with the suction aspect, while the mass transfer rate drops with suction in both solutions. Abstract : Nanofluid is a novel heat transfer fluid with the ability to significantly improve the heat transfer efficiency of regular fluids. Many efforts have been made to study its viscosity and thermal conductivity, both of which are crucial thermophysical properties. This work reports the significance of nanofluid along with thermophoretic and Brownian motion phenomena on the Agrawal flow towards a stagnation point past a permeable moving disk. The impacts of the Maxwell velocity slip and Smoluchowski temperature conditions are also incorporated.…